Optical and Structural Properties of Thermally Evaporated Zinc Oxide Thin Films on Polyethylene Terephthalate Substrates - M. G. Faraj; K. Ibrahim (International Journal of Polymer Science)
Zinc oxide thin films of different thicknesses ranging from 100 to 300 nm were prepared on polyethylene terephthalate substrates with thermal evaporation in a vacuum of approximately 3×10-5 Torr. X-ray diffraction patterns confirm the proper phase formation of the material. From atomic force microscopy (AFM) images, it was found that the root mean square roughness of the film surface increased as the film thickness increased. The optical properties of ZnO on PET substrates were determined through the optical transmission method using an ultraviolet-visible spectrophotometer. The optical band gap values of ZnO thin films slightly decreased as the film thickness increased.